2015
DOI: 10.5194/acpd-15-6821-2015
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Changing shapes and implied viscosities of suspended submicron particles

Abstract: Abstract. The change in shape of atmospherically relevant organic particles is used to estimate the viscosity of the particle material without the need for removal from aerosol suspension. The dynamic shape factors χ of particles produced by α-pinene ozonolysis in a flow tube reactor, under conditions of particle coagulation, were measured while altering the relative humidity (RH) downstream of the flow tube. As relative humidity was increased, the results showed that χ could change from 1.27 to 1.02, correspo… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
61
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(67 citation statements)
references
References 50 publications
6
61
0
Order By: Relevance
“…This may result in a change in the material properties. In an effort to minimize biases due to these perturbations, we have employed a new optical method that provides a non-invasive probe of shape or structural anisotropy that may be present in solid or highly viscous semi-solid SOA particles (Virtanen et al, 2010;Adler et al, 2013;Pajunoja et al, 2014;Schill et al, 2014;Zhang et al, 2015), but that is quickly erased in low viscosity droplets as they relax E. Järvinen et al: Observation of viscosity transition in α-pinene secondary organic aerosol 4425 toward the most energetically favourable state, i.e., spherical droplets that are homogeneous throughout their volumes.…”
Section: Introductionmentioning
confidence: 99%
“…This may result in a change in the material properties. In an effort to minimize biases due to these perturbations, we have employed a new optical method that provides a non-invasive probe of shape or structural anisotropy that may be present in solid or highly viscous semi-solid SOA particles (Virtanen et al, 2010;Adler et al, 2013;Pajunoja et al, 2014;Schill et al, 2014;Zhang et al, 2015), but that is quickly erased in low viscosity droplets as they relax E. Järvinen et al: Observation of viscosity transition in α-pinene secondary organic aerosol 4425 toward the most energetically favourable state, i.e., spherical droplets that are homogeneous throughout their volumes.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have confirmed that organic aerosols, which comprise approximately half of the total submicron aerosol mass in the atmosphere, can change from liquid to glassy state at ambient humidity levels and temperatures (Zobrist et al, 2008;Virtanen et al, 2010;Shrestha et al, 2014;Zhang et al, 2015). The effect of temperature may be especially important when aerosol particles are lifted into the free troposphere, where the temperature change can rapidly alter their phase from liquid to glass .…”
Section: Introductionmentioning
confidence: 99%
“…RenbaumWolff et al (2013) studied the phase state and viscosity of the water-soluble part of α-pinene SOAs at several humidity levels and phase separation effects. Zhang et al (2015) characterized the viscosity of α-pinene SOAs across a wide range of relative humidity levels. Rothfuss and Petters (2017) studied the viscosities of sucrose particles with sodium dodecyl sulfate (SDS) particles up to 10 7 Pa under subfreezing temperature regimes.…”
Section: Introductionmentioning
confidence: 99%
“…CC BY 4.0 License. that its measured viscosities and calculated diffusion coefficients are lower than those of anthropogenic SOA by as much as orders of magnitude at comparable conditions (Song et al, 2016(Song et al, , 2018Zhang et al, 2015).…”
Section: Introductionmentioning
confidence: 90%
“…engulfed" organic-inorganic morphology; an "island" morphology, where discrete pockets of SOA dot a larger inorganic particle; and a "core-shell" morphology, characterized by an organic rich outer "shell" and aqueous inorganic "core" (Freedman, 2017;O'Brien et al, 2015;Price et al, 2015;Renbaum-Wolff et al, 2016;Song et al, 2015Song et al, , 2016You et al, 2012;Zhang et al, 2015Zhang et al, , 2018a. Pye et al (2018) applied the Aerosol Inorganic-Organic Mixtures Functional groups Activity Coefficients (AIOMFAC) model (Zuend et al, 2008) to predict the thermodynamic favorability of phase separation in SOA using a box model and found that aerosols over the southeastern United States may be phase separated as frequently as 70% of the time.…”
Section: Introductionmentioning
confidence: 99%